2005
DOI: 10.1038/nature03836
|View full text |Cite
|
Sign up to set email alerts
|

Conditional telomerase induction causes proliferation of hair follicle stem cells

Abstract: TERT, the protein component of telomerase 1,2 , serves to maintain telomere function through the de novo addition of telomere repeats to chromosome ends and is reactivated in 90% of human cancers. In normal tissues, TERT is expressed in stem cells and in progenitor cells 3 , but its role in these compartments is not fully understood. Here, we show that conditional transgenic induction of TERT in mouse skin epithelium causes a rapid transition from telogen, the resting phase of the hair follicle cycle, to anage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
354
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(377 citation statements)
references
References 30 publications
19
354
2
2
Order By: Relevance
“…In addition, the ST antigen has been shown to activate Notch, Hedgehog and Wnt pathways (Ali-Seyed et al, 2006) all of which are associated with stem cell self-renewal as well as breast carcinogenesis (Liu et al, 2005). Furthermore, overexpression of telomerase is also known to enhance proliferation of adult stem cells (Sarin et al, 2005). Thus, the introduced oncogenes are likely to have contributed to the long-term stemness properties of NBLE cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ST antigen has been shown to activate Notch, Hedgehog and Wnt pathways (Ali-Seyed et al, 2006) all of which are associated with stem cell self-renewal as well as breast carcinogenesis (Liu et al, 2005). Furthermore, overexpression of telomerase is also known to enhance proliferation of adult stem cells (Sarin et al, 2005). Thus, the introduced oncogenes are likely to have contributed to the long-term stemness properties of NBLE cells.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, deletion of Terc results in decreased lifespan after several generations (Rudolph et al, 1999), implicating telomerase components as longevity factors. Interestingly, distinct from its action in telomere maintenance, TERT regulates the mobilization and proliferation of epidermal stem cells in the hair follicle (Flores et al, 2005;Sarin et al, 2005). Consistent with its prominent role in stem cell proliferation independent of its reverse transcriptase activity, TERT is a pivotal component of the transcriptional complex downstream of WNT signaling (Choi et al, 2008;Park et al, 2009).…”
Section: Foxo Transcription Factors In Adult Stem Cells: Integrating mentioning
confidence: 99%
“…Together, these data point out to a role of telomeres in the regulation of HSC homeostasis 102 . Two recent studies investigated the effects of telomerase and telomere length on epidermal stem cell behaviour 103,104 . Using different constitutive and inducible transgenic mouse models, authors demonstrated that telomere length and telomerase activity are independent determinants of the mobilization efficiency and proliferative capacity of epidermal stem cells.…”
Section: Telomerase Activity and Telomere Length Regulate Cancer Stemmentioning
confidence: 99%